TINJAUAN HUKUM ISLAM TERHADAP MAHAR DALAM PERKAWINAN ISLAM - Nurul Amalia; Nur Irmayanti Umar (IAI DDI Mangkoso, 2024)
This article discusses the legal and social aspects of dowries in marriage, focusing on the provisions of Law No. 1 of 1974 and Government Regulation No. 9 of 1975, about as well as the influence of local customs such as